Intellectual Property Management in a Higher Education Institution: a literature review - Nakamura, Márcio Akio (2024)
The university is an institution with the potential to promote innovation in collaboration with government and industry, in the triple helix model. The intellectual assets created in the university environment need a management system as well as protection. The aim of this research is to identify and characterize the forms of Intellectual Property (IP) Management proposed in the literature for Higher Education Institutions (HEIs). The method used was a systematic review of the literature, using the Prisma Protocol. Searches were carried out in the Capes and Scopus journal databases, and 9 articles were selected to make up the scope of the research. The results show that IP management involves external and internal policies favorable to innovation, with stakeholder engagement being essential. IP management is carried out in a number of ways, most notably the transfer of technologies through offices. Tools such as benchmarking, courses and training are used.